Impact of hepatitis B virus and hepatitis C virus infection on sperm parameters of infertile men - Sana karamolahi; Reza Salman Yazdi; Mehrangiz Zangeneh; Mahin Jamshidi Makiani; Behnam farhoodi; Mohammad Ali Sedighi Gilani (Shahid Sadoughi University of Medical Sciences, 2019)
Background Viral hepatitis is one of the health problems which have the effects on the health issues. It seems that hepatitis B virus (HBV) and hepatitis C virus (HCV) infection have negative impacts on the semen quality and male infertility rate. Objective In this study, we aimed to evaluate the effects of HBV and HCV on sperm quality among Iranian infertile men referred to Royan Institute Reproductive Biomedicine Research Center between 2003 and 2014. Materials and Methods This retrospective case-control study included 112 HBV positive infertile men and 47 HCV positive infertile men as case group and 112 HBV negative and HCV negative matched infertile men as a control group. All semen analysis and viral parameters assessment was performed in the central laboratory with the same method and instruments. Results Sperm count among infertile men with HBV and HCV infection was significantly lower than control group [the mean of the total sperm count 100.95░±░118.59, 118.22░±░141.18, 166.27░±░151.25 (p░<░0.001)]. Sperm motility was significantly decreased in HBV and HCV positive men in comparison to the control group [30.97░±░25.88, 31.09░±░28.72, 40.87░±░23.37, respectively (p░<░0.007)]. The percentage of normal sperm morphology was significantly higher in control group in comparison to HBV and HCV infected group [the mean of the normal semen morphology 3.23░±░3.27, 3.70░±░3.83, 4.51░±░3.15 p░<░0.015]. Although there is a significant decline in liquefaction time in the case group but the viscosity, semen volume, and PH of semen samples were similar in the both case and control groups. Conclusion Our results suggest that HBV and HCV infection are associated with poor sperm quality.